2022
DOI: 10.1039/d2ra03286d
|View full text |Cite
|
Sign up to set email alerts
|

Precise immunological evaluation rationalizes the design of a self-adjuvanting vaccine composed of glycan antigen, TLR1/2 ligand, and T-helper cell epitope

Abstract: Detailed analysis of a three-component self-adjuvanting vaccine revealed that conjugate vaccines can be designed to achieve the desired immune responsesviabottom-up construction of the necessary immune elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…The lipopeptide Pam 3 CSK 4 is one of the most widely employed TLR1/2 agonists and has been extensively applied in various antitumor and antiviral vaccines as adjuvant for immune response augmentation. Furthermore, previous studies have also reported that covalently linking TLR1/2 agonists to peptide or protein antigens significantly enhanced their immunogenicity, thereby eliciting potent antigen-specific immune responses. Additionally, lipidation is a post-translational modification with significant clinical relevance, especially in the drug development and design of therapeutic agents . In vaccine design, lipid modification of peptides or protein antigens can effectively facilitate the self-assembly and aggregation of antigens, thereby enhancing their uptake by antigen-presenting cells, consequently strengthening antigen-specific immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…The lipopeptide Pam 3 CSK 4 is one of the most widely employed TLR1/2 agonists and has been extensively applied in various antitumor and antiviral vaccines as adjuvant for immune response augmentation. Furthermore, previous studies have also reported that covalently linking TLR1/2 agonists to peptide or protein antigens significantly enhanced their immunogenicity, thereby eliciting potent antigen-specific immune responses. Additionally, lipidation is a post-translational modification with significant clinical relevance, especially in the drug development and design of therapeutic agents . In vaccine design, lipid modification of peptides or protein antigens can effectively facilitate the self-assembly and aggregation of antigens, thereby enhancing their uptake by antigen-presenting cells, consequently strengthening antigen-specific immune responses.…”
Section: Introductionmentioning
confidence: 99%